Effect of Cholesterol on C99 Dimerization: Revealed by Molecular Dynamics Simulations - Li, Cheng-Dong; Junaid, Muhammad; Shan, Xiaoqi; Wang, Yanjing; Wang, Xiangeng; Khan, Abbas; Wei, Dong-Qing (Frontiers in Molecular Biosciences, 2022)
C99 is the immediate precursor for amyloid-beta (Aβ), and therefore is a central intermediate in the pathway that is believed to result in Alzheimer's disease (AD). It has been suggested that cholesterol associates with C99, but the dynamic details of how cholesterol affecting C99 assembly and the Aβ formation remain unclear. To investigate this question, we employed the coarse-grained (CG) and all-atom (AT) molecule dynamics (MD) simulations to study the effect of cholesterol and membrane composition on C99 dimerization. We find that although the existence of cholesterol delays C99 dimerization, there is no direct competition between C99 dimerization and cholesterol association. By contrary, the existence of cholesterol makes C99 dimer more stable, which presents a cholesterol binding C99 dimer model. Cholesterol and membrane composition change the dimerization rate and conformation distribution of C99, which will subsequently influence the production of Aβ. Our results provide insights into the potential influence of physiological environment on the C99 dimerization, which will help us understand Aβ formation and AD’s etiology.